1983
DOI: 10.1093/bja/55.11.1113
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Physiotherapy for Postoperative Pulmonary Complications

Abstract: A prospective randomized controlled trial was conducted in patients undergoing elective cholecystectomy to assess the value of routine chest physiotherapy. One hundred and two patients entered the study: 47 patients developed no pulmonary complications, 29 had pulmonary atelectasis and a further 26 developed chest infection. The pattern of changes in arterial oxygen tension in the period after operation supported the clinical allocation of the patients. Of 51 patients not receiving physiotherapy, 11 developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The incidence of lower respiratory tract infections increased across resection strata which may reflect increasing risk of aspiration with increasing proximity of the resection to the airway. This is a useful intervention target in head and neck cancer as intensive physiotherapy can reduce the incidence of postoperative pulmonary complications . By contrast, the incidence of pneumothorax were very similar between all strata except pharyngolaryngectomy where its incidence was almost three times higher than for the other strata.…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of lower respiratory tract infections increased across resection strata which may reflect increasing risk of aspiration with increasing proximity of the resection to the airway. This is a useful intervention target in head and neck cancer as intensive physiotherapy can reduce the incidence of postoperative pulmonary complications . By contrast, the incidence of pneumothorax were very similar between all strata except pharyngolaryngectomy where its incidence was almost three times higher than for the other strata.…”
Section: Discussionmentioning
confidence: 95%
“…Quanto à força muscular inspiratória, estudo realizado por Bellinetti e Thomson 1 relaciona a função muscular respiratória anormal -no período pré-operatório -e a diminuição dessa força -no pós-operatório -à piora da função pulmonar, com consequente maior incidência de complicações pulmonares. Neste estudo, Embora tenham sido feitos poucos estudos controle, Roukema et al 21 encontraram uma redução estatisticamente significativa de 50% das complicações, com a aplicação de padrões ventilatórios ou uso do inspirômetro de incentivo ou RPPI, e Morran et al 22 conseguiram uma diminuição significativa na incidência da pneumonia pós-operatória com aplicação de padrões ventilatórios.…”
Section: Resultsunclassified
“…Much of the early evaluation of IS was conducted in the 1980s, and use of IS after abdominal surgery was shown to be beneficial in several clinical trials. In comparing IS with care without pulmonary therapy after abdominal surgery, results showed significant reductions in pulmonary complications 9–11 and, more recently, an improvement in oxygen saturation 12 . In a 1994 systematic review and meta‐analysis of pulmonary therapies after upper abdominal surgery, Thomas and McIntosh 13 found that IS was more effective than no physical therapy intervention in the prevention of postoperative pulmonary complications, but there was no significant difference between IS, intermittent positive pressure breathing (IPPB), and deep breathing exercises.…”
mentioning
confidence: 99%